2012
DOI: 10.1155/2012/637187
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Celiac Disease: From Recognizing to Managing

Abstract: The nonclassic clinical presentation of celiac disease (CD) becomes increasingly common in physician's daily practice, which requires an awareness of its many clinical faces with atypical, silent, and latent forms. Besides the common genetic background (HLA DQ2/DQ8) of the disease, other non-HLA genes are now notably reported with a probable association to atypical forms. The availability of high-sensitive and specific serologic tests such as antitissue transglutuminase, antiendomysium, and more recent antidea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
68
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 81 publications
(129 reference statements)
0
68
0
5
Order By: Relevance
“…La frecuencia de la enfermedad propiamente tal se estima actualmente en ~0,5% de la población chilena, en contraste a la prevalecía de 1:1.800 que se conocía anteriormente en base a los casos diagnosticados a propósito de su consulta al especialista 17 . Esta práctica de buscar activamente a los pacientes, sin esperar a que consulten, ha tenido dos consecuencias interesantes: los familiares de primer grado de celíacos, diagnosticados por búsqueda activa, representan alrededor de 10-15% de los casos actualmente diagnosticados; por otra parte, la proporción de casos diagnosticados ha aumentado considerablemente entre los adultos, con una disminución relativa de casos cuya sintomatología principal es diarrea durante la edad pediátrica 18,19 .…”
Section: ¿En Quienes Debemos Buscar Enfermedad Celíaca?unclassified
“…La frecuencia de la enfermedad propiamente tal se estima actualmente en ~0,5% de la población chilena, en contraste a la prevalecía de 1:1.800 que se conocía anteriormente en base a los casos diagnosticados a propósito de su consulta al especialista 17 . Esta práctica de buscar activamente a los pacientes, sin esperar a que consulten, ha tenido dos consecuencias interesantes: los familiares de primer grado de celíacos, diagnosticados por búsqueda activa, representan alrededor de 10-15% de los casos actualmente diagnosticados; por otra parte, la proporción de casos diagnosticados ha aumentado considerablemente entre los adultos, con una disminución relativa de casos cuya sintomatología principal es diarrea durante la edad pediátrica 18,19 .…”
Section: ¿En Quienes Debemos Buscar Enfermedad Celíaca?unclassified
“…Research has found an increased incidence of coeliac disease in those with Wilson's disease, diabetes (Admou et al, 2012), hypothyroidism, Williams syndrome (4%; Mihci et al, 2015), Turners syndrome (4%; Dias Mdo et al, 2010) and Down's syndrome (Henderson et al, 2007).…”
mentioning
confidence: 99%
“…Trends across studies from a range of countries have pointed to a consensus of around 6% of individuals with Down's syndrome who have coeliac disease (Szaflarska-Popławskaet al, 2016;Nisihara et al, 2005;Roizen et al, 2014;Goldacre et al, 2004;Nisihara et al, 2005). This may prove to be a conservative estimate given the known underrepresentation due to atypical and latent coeliac disease (Admou et al, 2012) and diagnostic over shadowing within people who have cognitive impairments.…”
mentioning
confidence: 99%
See 2 more Smart Citations